The role of labour ministries in the improvement of labour-management relations in Latin America. Docuement prepared by the I.L.O. and submitted to the Conference of Labour Ministers of the Member States of the Organisation of American States (Bogotá, 1963) and recommendations adopted by the Conference (International Labour Office, 1964)
Stencil.